An empirical analysis of factors influencing continuance intention of mobile instant messaging in China. (September 2016) - Gan, Chunmei
The purpose of this research is to investigate factors affecting users' continuance intention in the context of mobile instant messaging (IM). Drawing upon the social cognitive perspective, the study builds a theoretical model to illustrate the relationships between perceived user base, habit, resistance to change and continuance intention. An empirical study is conducted to test the research model by surveying Chinese mobile IM users. The results show that habit and resistance to change both play important roles in intention to continue use of mobile IM. More specifically, resistance to change is found to have the largest effect on continuance intention. The results also show that habit directly and indirectly affects continuance intention through resistance to change. In addition, perceived user base has a significant effect on continuance intention. Extant information system (IS) continuance research has mainly focused on contexts other than mobile IM. Furthermore, prior IM-related studies have tended to focus more on investigation of factors affecting IM usage behavior and have paid less attention to user continuance of mobile IM services. This current study attempts to address this research gap. Specifically, the study proposes a model that integrates factors such as resistance to change, habit, perceived user base, and continuance intention in the context of mobile IM services. In addition, the study empirically demonstrates the effects of resistance to change and habit on continuance intention, as well as the influence of habit on resistance to change.